2012
DOI: 10.1179/1743281211y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sinter properties and iron ore granulation index

Abstract: A range of iron ores were used in varying proportions to prepare 28 different ore mixtures. Each mixture was classified according to its granulation index and sintered in a pilot plant. The resulting sinters were characterised by chemical analysis, degradation during reduction in the blast furnace (reduction degradation index test), cold strength (tumbler test), coke consumption and process productivity. Sinter quality was assessed in relation to the granulation index of the ore mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…10 In addition, the effects of particle size distribution of iron ores on granulation performance were widely researched. [11][12][13] However, specific characteristics of particle size have not been proposed to assess the granulation performance. This paper describes setting up a practical structural model of granules, and finding out the method to optimise the granulation through studying the factors influencing granulation.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, the effects of particle size distribution of iron ores on granulation performance were widely researched. [11][12][13] However, specific characteristics of particle size have not been proposed to assess the granulation performance. This paper describes setting up a practical structural model of granules, and finding out the method to optimise the granulation through studying the factors influencing granulation.…”
Section: Introductionmentioning
confidence: 99%
“…Cores et al further set an upper limit of 8 mm for nuclear particles and classified iron ore into four groups based on G-index, with Group A having a G-index less than 15, Group B having a G-index between 15 and 35, Group C having a G-index between 35 and 70, and Group D having a G-index greater than 70. The use of different groups of iron ore together is beneficial for regulating the granulation properties and improving the sinter strength index 13,65) . Although the presence of iron ore ultrafine powder can help the quasi-particle size to grow, it does not significantly affect the quasi-particle strength, which is mainly controlled by the adhesion force of the liquid bridge 66) .…”
Section: 11: Iron Oresmentioning
confidence: 99%
“…The main literature that offers the samples used in the present study is shown in Table 1. In addition, the sample set was also built with some other references [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The correlation analysis of the sample set is shown in Figure 1, which revealed that there was a strong correlation between tumbler index (TI) and CaO content and ignition temperature (IT), an increase of CaO content or ignition temperature could increase the sinter drum strength when other experimental conditions were fixed.…”
Section: Samples Setmentioning
confidence: 99%